A Class of Highly Concentrated Time-Frequency Distributions Based on the Ambiguity Domain Representation and Complex-Lag Moment. (19th July 2009) - Orović, Irena; Stanković, Srdjan
Abstract : A class of time-frequency distributions with complex-lag argument is proposed. It is based on the ambiguity domain representations of real and complex-lag moment, combined to provide a cross-terms free representation for multicomponent signals. Furthermore, the distributions from the proposed class provide a more effective instantaneous frequency estimation for signals with fast varying phase function than the existing approach. The theory is illustrated by the examples.